Prescription pattern of antimicrobial agents in a teaching hospital of South India - Khade, Ajay M.; Bashir, M Shakeel M; George, Savya; Annaldesh, Sheethal; Bansod, Kishor A. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Use of irrational and unnecessary antimicrobials remains common in the developing countries. The present study was conducted to evaluate the use of antimicrobial agents in the tribal district hospital of Andhra Pradesh India. Methods: In this retrospective study, 200 hospitalized cases from medicine, surgery, obstetrics and gynaecology and paediatrics departments were randomly selected. Results: Most common diagnosis was febrile illness (15%) followed by gastroenteritis (10%) and malaria (8%). Antimicrobials were used in 57% cases. All the cases were managed by empirical treatment. Cefixime (40%) was the most common antimicrobial followed by ampicillin (32.50%), metronidazole (30%) and ciprofloxacin (26.50%). Use of antimicrobial monotherapy (41.67%) and 2 drug therapy (36.46%) was common. Conclusion: Empirical use of higher antimicrobial agents is routine and cheap antimicrobials like ampicillin are still most useful drugs in the region. There is a need of specific essential drug list for the region.